Entrepreneurial Success Factors of Small and Medium Size Women Enterprises in Kathmandu (The Spectrum, 2024)
This study examines the personal and external factors affecting the success of women entrepreneurs in Kathmandu Valley. To achieve the research objective, the data were collected from the primary source mainly through a structured questionnaire under convenience sampling basis from 384 women entrepreneurs in Kathmandu Valley. Descriptive and inferential statistics have been used to develop the breadth and depth of the study. The results of the study revealed a positive significant association of personal and external factors with the success of women entrepreneurs. The study found stronger factors self-confidence, need for achievement, and risk-propensity. In addition, the study revealed social-cultural factors as the external factors detrimental to women entrepreneurs’ success. This study contributes to the existing theory of entrepreneurial success by incorporating personal and external factors in a holistic approach.